IMPLEMENTASI KEBIJAKAN KEAMANAN DAN KETERTIBAN LAPAS DALAM MENEKAN TINDAK KRIMINA DI DALAM LEMBAGA PEMASYARAKATAN KELAS IIB ANAK AIR PADANG: - Muhammad Iqbal; Hasbullah Malau (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This research aims to analyze the implementation of security and order policies in suppressing criminal acts in the Anak Air Padang Class IIB Correctional Institution. The research is based on the fact that various violations and criminal acts are still found in prisons even though regulations and operational standards have been implemented. The research uses a qualitative method with a descriptive approach through interview, observation, and documentation. Data analysis is carried out using George C's policy implementation theory. Edwards III which includes communication, resources, executive disposition, and bureaucratic structure. The research results show that the security and order policy has been implemented in accordance with the applicable provisions, but it is not optimal due to limited human resources, overcrowding conditions, and limited security facilities. The main contribution of this study lies in strengthening the analysis of the implementation of security policies in correctional institutions as a total institution, as well as the provision of policy recommendations that are applicable in nature for improving the correctional security system.